Proceedings of the 2nd International Symposium on Asia Urban GeoEngineering (Springer Series in Geomechanics and Geoengineering,, 2018)
This book contains the keynote presentations, invited speeches, and general session papers presented at the 2nd International Symposium on Asia Urban GeoEngineering, which will be held from 24 November to 27 November 2017 in Changsha, China. The contents will cover the topics of (i) Fundamental behavior and constitutive model of geomaterials, (ii) Excavation and slope engineering, (iii) Tunnel and underground engineering, (iv) Foundation and foundation treatment, (v) Environmental geotechnical engineering, (vi) Numerical methods in geotechnical engineering. It will provide an opportunity to share knowledge and experiences of the analysis, design, construction, and maintenance of urban geoengineering among engineers, researchers, and professors in Asian countries. It will improve our knowledge of requirements of geoengineering for a long-term sustainable urban development and the need to protect and preserve our environment.